Cerebral venous sinus thrombosis in scrub typhus infection: A rare presentation - Sardana, Vijay; Shringi, Prashant (Indian Journal of Case Reports, 2019)
Scrub typhus is an acute febrile infectious illness caused by Rickettsia species Orientia tsutsugamushi. Scrub typhus has diverse clinical manifestations ranging from a non-specific febrile illness to severe multiorgan dysfunction. A spectrum of neurological complications in scrub typhus includes aseptic meningitis, meningoencephalitis, cerebellitis, myelitis, cerebral hemorrhage, and cerebral infarction. This report describes the case of a scrub typhus with cerebral venous sinus thrombosis, an unreported complication of scrub typhus to the best of our knowledge.